2007
DOI: 10.1158/1078-0432.ccr-07-1506
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell Number and Prognosis in Progressive Castration-Resistant Prostate Cancer

Abstract: Purpose: The development of tumor-specific markers to select targeted therapies and to assess clinical outcome remains a significant area of unmet need. We evaluated the association of baseline circulating tumor cell (CTC) number with clinical characteristics and survival in patients with castrate metastatic disease considered for different hormonal and cytotoxic therapies. Experimental Design: CTC were isolated by immunomagnetic capture from 7.5-mL samples of blood from 120 patients with progressive clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
460
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(474 citation statements)
references
References 29 publications
11
460
0
3
Order By: Relevance
“…Assessment of CTC using CellSearch has been cleared by the Food and Drug Administration as a prognostic indicator, in conjunction with other clinical methods, for patients with metastatic breast, prostate, and colorectal cancers. Studies in metastatic breast, colorectal, and prostate cancer showed that patients about to start new lines of chemotherapy could be divided into groups with favourable and unfavourable prognosis on the basis of the number of CTCs measured with the analytically valid CellSearch system(Veridex, Raritan, NJ, USA) [3,[5][6][7][8][9][10][11][12][13]20]. When studying the association between the number of CTCs and evolution of the disease, researchers generally use a single cutpoint to identify favorable and unfavorable response groups, such as 5 CTCs for MBC [3,4,14], three for metastatic colorectal cancer [11], and five for castration resistant prostate cancer [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of CTC using CellSearch has been cleared by the Food and Drug Administration as a prognostic indicator, in conjunction with other clinical methods, for patients with metastatic breast, prostate, and colorectal cancers. Studies in metastatic breast, colorectal, and prostate cancer showed that patients about to start new lines of chemotherapy could be divided into groups with favourable and unfavourable prognosis on the basis of the number of CTCs measured with the analytically valid CellSearch system(Veridex, Raritan, NJ, USA) [3,[5][6][7][8][9][10][11][12][13]20]. When studying the association between the number of CTCs and evolution of the disease, researchers generally use a single cutpoint to identify favorable and unfavorable response groups, such as 5 CTCs for MBC [3,4,14], three for metastatic colorectal cancer [11], and five for castration resistant prostate cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) have been shown to be an independent prognostic factor in metastatic breast cancer (MBC) [3][4][5][6], in metastatic prostate cancer [7][8][9][10] and in metastatic colorectal cancer [11,12]. They represent a promising tool for therapeutic monitoring: an elevated number of CTCs measured at any time in the clinical course were associated with a high likelihood of a very short time to progression.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that AA interacts with adipogenic differentiation pathways, inducing a proportional increase in adipocyte numbers. Thus, in the presence of specific lipids, the number of BM-Ad will increase, potentially augmenting the chemoattractive stimulus of migrating cancer cells known to be in circulation in escalating numbers as cancer load increases (Danila et al, 2007) and increasing the statistical chance of 'proximity' encounters between migrating cancer cells and BM-Ad. Thus, in a 'Darwinian' sense, the 'fitness' of the cancer cell to survive and propagate in red BM is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation with survival, using the Veridex technology, has been demonstrated in breast cancer 15,16 colorectal cancer 31 and castration resistant prostate cancer. 32 Animal studies have shown a correlation between the number of CTC's and the number of lung metastases and tumor burden 33 although this has not been confirmed in cancer patients where, in at least one study, a correlation between radiographic tumor volume and CTC's was not found. 34 If, with further studies, the number of CTC's proves not to be correlated with either the number of metastatic sites or the cumulative tumor burden, then other potential biological correlates will need to be explored including, but not limited to, adhesiveness, vascular permeability, and immune mediated interactions with both macroscopic tumor and circulating tumor cells.…”
Section: Discussionmentioning
confidence: 99%